Implementing HL7: from the Standard's Specification to Production Application - Schadow, G.; Föhring, U.; Tolxdorff, Th. (Methods of Information in Medicine, 1998)
A C++ implementation of the HL7 health-care data interchange standard was developed by automatic methods applied to the authoritative specification of the standard. The reusable class library th us created presents an intuitive, flexible, and easy-to-use application programming interface to the HL7 protocol. This allows HL7 applications to be developed quickly while a high conformance to the standard is ensured.
Keywords: HL7; Electronic Data Interchange; Standardization